Noticia medieval de una bestia mítica china en un viajero navarro y uno andalusí - Izcue Argandoña, Javier (Huarte de San Juan. Geografía e Historia, 2006)
This article presents and comments on the references made by two Spanish travellers –Benjamínde Tudela, jewish, and Abu-Hamid, a muslim from Gramada– of a mythical bird which was thought to have a Chinese origin. This imaginary animal receives different names such as simurgh, gryphon, roc... until it becames part of the Western imaginary thought due to the Mediaeval Christian Bestiary. Various interpretations about textual transmission of this animal image and its different meanings and symbolic values are considered.